Penyuluhan Deteksi Dini Stunting Pada Anak Usia Sekolah di Puskesmas Tiban Baru - Hazen Azis; Siti Husaidah, Mona Rahayu Putri, Sri Dewi Haryati, Desi Pramita Sari (Adiba Aisha Amira, 2021)
Stunting is a chronic nutritional problem in toddlers which is characterized by a shorter height compared to children his age. The incidence of short toddlers or commonly called stunting is one of the nutritional problems experienced by toddlers in the world today. In 2017, 22.2% or around 150.8 million children under five in the world were stunted. Data on the Proportion of Stunting in the Riau Islands Province shows that the Stunting incidence data is already below the national target of only 16.82%. The most visible factor in the community is the mother's lack of knowledge about the nutrients that must be met by the child during the growth period. Mothers usually give delicious food to their children without knowing whether the food contains sufficient nutrients or not, and does not compensate for it with healthy foods that contain lots of nutrients. As many as 25 people who were present during the counseling were able to understand and understand the material presented by the presenter regarding stunting. The whole community who attended was in general good health and the children looked active and healthy.